Wearable-Supported Stroke Telerehabilitation in Saudi Health Centres: A 12-Week Single-Arm Feasibility and Implementation Pilot - Abdulaziz Althuwayfiri (Journal of Intelligent Decision Making and Information Science, 2026)
Introduction: Post-discharge stroke rehabilitation often depends on intermittent clinic visits and patient or caregiver self-report, limiting clinicians’ ability to monitor home exercise participation, physiological response, and early warning signs. This study evaluated the feasibility, safety, and implementation value of a wearable digital wristband-enabled telerehabilitation model for stroke survivors managed through Saudi health centres. Material and methods: A 12-week single-arm feasibility and implementation pilot was conducted with 27 adult stroke survivors medically cleared for home exercise and able to use a smartphone and wristband independently or with minimal assistance. The intervention combined wearable monitoring of heart rate, activity, steps, active minutes, and wear time with a structured home rehabilitation programme, clinician dashboard review, feedback, and escalation for abnormal alerts or poor exercise tolerance. Outcomes included recruitment, retention, adherence, wearable use, monitoring completeness, data quality, safety, exploratory functional outcomes, and clinician workflow indicators. Results: Recruitment yield was 79.4%, week-12 retention was 92.6%, and 84.0% of scheduled home rehabilitation sessions were completed. Mean valid wearable use reached 5.4 days per week, and monitoring-complete participant-weeks reached 88.1%. No intervention-related serious adverse events were recorded. Paired exploratory outcomes improved across mobility, walking endurance, functional independence, balance, and stroke-specific quality of life. Clinician review time decreased by 47.8%, dashboard data completeness increased from 58.2% to 89.4%, and alert response time decreased by 55.1%. Conclusions: Wearable-supported telerehabilitation was feasible, operationally safe, and potentially useful for structured home-based follow-up after stroke. Larger controlled multicenter studies are required to confirm clinical effectiveness, cost-effectiveness, long-term adherence, and scale-up readiness.